Shipping Emissions and Air Pollution: Latest Methodological Developments and Applications - Yuanqing Zhu; Long Liu (Atmosphere, 2023)
Shipping, which accounts for over 80% of international trade transportation, is the most cost-effective and efficient mode of transportation [...]